Managing learning trajectories: the case of 14-19 mathematics - Noyes, Andrew; Sealey, Paula (Taylor and Francis Group, 2011)
In this paper we explore how mathematics department leaders manage curriculum (what is taught), teaching (how it is taught) and learner progression (what results) for 14-19 year olds. The background to the study is a range of national, and international, concerns about participation rates in university entrance level mathematics. Given the recommendation of the Smith Report (2004) that new pathways models be developed for 14-19 mathematics, this paper explores some of the strategies employed, and issues faced, by schools as they seek to maximise attainment and participation in mathematics. Following a thematic analysis of data from interviews with heads of department in fifteen schools we look in more depth at one school to see how it manages the mathematics learning trajectories of young people. The theme of performativity is all pervasive.